PEMBENTUKAN DAN PELATIHAN KADER REMAJA PEDULI ASI (REMDULSI) - Aulia Fatmayanti; Kuswanto Kuswanto; Yanik Muyassyaroh; Anjar Astuti; Marlynda Happy Nurmalita Sari (Universitas Kadiri, 2019)
Adolescents are one of the communities that can support the success of exclusive breastfeeding. Adolescents who are members of youth and youth groups can join in remdulsion (adolescents care about breast milk). The function of this group is to be able to help campaign for the success of exclusive breastfeeding and can also be a regeneration. To join the community and help the success of the exclusive breastfeeding campaign certainly requires good knowledge about breastfeeding in adolescents. During the preliminary survey, the servants interviewed 5 teenagers in the village of Karangjati. From the results of the interview, it was found that teenagers did not know about exclusive breastfeeding, including the benefits of breastfeeding, the limit of exclusive breastfeeding for infants and mothers.